Gold nanoparticle-loaded filter paper: a recyclable dip-catalyst for real-time reaction monitoring by surface enhanced Raman scattering1. Issue 22 (18th March 2015) - Zheng, Guangchao; Polavarapu, Lakshminarayana; Liz-Marzán, Luis M.; Pastoriza-Santos, Isabel; Pérez-Juste, Jorge
<x xml:space="preserve">Abstract</x> While acting as catalysts, Au NP-loaded paper composites display excellent surface enhanced Raman scattering (SERS) efficiency, allowing the real-time monitoring of chemical reactions.